Strategi Program Revitalisasi Kantor Urusan Agama Dalam Meningkatkan Layanan Keagamaan Masyarakat - Aditya Rahmat Nandito; Hidayat Hidayat (Social Science and Contemporary Issues Journal, 2024)
This thesis is entitled "Strategy for the Revitalization Program for the Office of Religious Affairs in Improving Community Religious Services in Muara Pinang District, Empat Lawang Regency". The revitalization of the Kua sub-district religious affairs office is a priority program of the Minister of Religion of the Republic of Indonesia. The Empat Lawang Regency Ministry of Religion office has implemented the program, especially in Kua, Muara Pinang sub-district. The purpose of this research is to determine the strategy for the revitalization program of the sub-district religious affairs office in improving community religious services and to determine the supporting and inhibiting factors in the religious services of the Muara Pinang sub-district religious affairs office, Empat Lawang district. This type of research is field research with a qualitative approach. There are two data sources used, namely primary and secondary data sources. Data collection techniques through observation, interviews and documentation. The location of this research is Muara Pinang Baru village, Jl. Prince, Muara Pinang sub-district, Empat Lawang district. According to Miles and Huberman, the data analysis technique used is in three stages, namely data reduction, data display, conclusion drawing/verification. The theory used is according to Minister of Religion Decree number 758 of 2021 concerning the revitalization of the religious affairs office, formulating six strategies for increasing institutional capacity, improving service standards, digital transformation of services, improving the quality of human resources, strengthening regulations and strengthening integration. The results of this research are the strategies carried out by the Muara Pinang sub-district religious affairs office, namely by changing the service profile at the KUA which has been documentation and administration in nature to become oriented towards community needs, in the form of guidance, services, consultation and assistance on family and religious issues as well as for active and responsive in service to describe the Kua revitalization program strategy in its implementation of providing community religious services. The evaluation uses stages in the dimensions of public service quality in the form of tangibility, reliability, assurance, empathy, responsiveness in providing religious services to the community in order to expect excellent service quality for the needs of the community. There are obstacles in the form of problems, namely human resources that are still lacking, facilities and infrastructure that are still inadequate both in terms of effectiveness and comfort in providing religious services to the community. The kua revitalization policy that has been implemented is still not optimally implemented.